Why aren’t we trusting one another? An autoethnography about third space leadership - Rachael Hains-Wesson (Journal of Learning Development in Higher Education)
The emergence of blended professionals in higher education who encompass roles such as academic, teaching-focused, learning design, academic development, and professional staff has led to a growing presence of third spaces where traditional boundaries between roles are blurred. These spaces require novel approaches to collaboration, leadership, and role management. This article explores the author’s self-study reflections via autoethnography as a now senior leader, looking back on their experiences as an early career third space academic at an Australian university. Employing a retrospective autoethnography, the study delves into the challenges and opportunities of managing a diverse team of third space professionals for the first time. The author’s lived experience highlights strategies for building trust, clarifying roles, and improving communication among blended professionals operating in third spaces. Key findings identify some of the critical leadership requirements needed in third spaces, including trust-building, understanding of roles, resource and time management, effective communication, and recognition of individual and collective contributions. This study provides valuable insights into navigating third space leadership and offers guidance to enhance team dynamics in these increasingly prevalent roles.